Idiopathic Pulmonary Fibrosis - Surani, Salim; Rajasurya, Venkat (IntechOpen, 2022)
Idiopathic pulmonary fibrosis (IPF) affects 13-20 people per 100,000 population worldwide. In the United States, approximately 100,000 people have IPF with 30,000-40,000 new cases diagnosed annually. Diagnosis remains a challenge with a significant lag between symptoms onset and diagnosis. Delayed diagnosis and treatment can carry high morbidity and mortality. This book provides concise, easy-to-read, and up-to-date information as it relates to clinical presentation, diagnosis, and treatment of IPF. Despite, adequate treatment, the disease progresses, and a lung transplant is necessary in some cases. This book also discusses the role of lung transplants for IPF and its complications. It is a useful resource for primary care physicians, allied health professionals, hospitalists, and pulmonary physicians who take care of patients with IPF.